2016
DOI: 10.1515/ap-2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Ergasilus (Copepoda: Ergasilidae) from Geophagus altifrons and G. argyrostictus (Perciformes: Cichlidae) in the Brazilian Amazon

Abstract: A new species of ergasilid copepod, Ergasilus xinguensis n. sp., is described from females found on the gills of two cichlid fishes, Geophagus argyrostictus (Kullander, 1991) (type host) and G. altifrons (Heckel, 1840), from the Brazilian Amazon. The new species can be distinguished from congeners by the unique combination of the following characteristics: the cephalothorax is not inflated and is slightly constricted, the first antennulary segment bears 3 setae, maxillule with 3 unequal outer setae without min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…However, Ergasilus spp. have infested species of Characidae, Pimelodidae, Anostomidae and Cichlidae from the Amazon (TAVARES-DIAS et al, 2015;TABORDA et al, 2016). Twenty-two freshwater species of Ergasilus are known from the gills of Neotropical fish (TABORDA et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, Ergasilus spp. have infested species of Characidae, Pimelodidae, Anostomidae and Cichlidae from the Amazon (TAVARES-DIAS et al, 2015;TABORDA et al, 2016). Twenty-two freshwater species of Ergasilus are known from the gills of Neotropical fish (TABORDA et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The gills were removed and analyzed using a stereomicroscope. The crustaceans found were fixed in 70% ethyl alcohol with 10% glycerin (EIRAS et al, 2006) and were then identified (LUQUE et al, 2013;TABORDA et al, 2016). The ecological terms used were those recommended by Bush et al (1997).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, Argulus elongatus Heller, 1857, and Dolops reperta Bouvier, 1899, were the most prevalent. However, Ergasilus xinguensis Taborda, Paschoal & Luque, 2016, was the most abundant species, even though it only infested the cichlids Crenicichla johanna Heckel, 1840, Crenicichla cincta Regan, 1905and Geophagus camopiensis Pellegrin, 1903, and sciaenid Plagioscion squamosissimus Heckel, 1840 (Table 2). Branchiurans Table 2.…”
Section: Introductionmentioning
confidence: 99%
“…Ergasilidae is one of the largest families of Cyclopoida, and most species are found on freshwater fish (Tavares-Dias et al 2015). Only adult females of ergasilids are parasites on gills, fins, the interior nasal fossae, or embedded in host tissues or in the urinary bladder of teleost fish species, and rarely on the gills of elasmobranchs and bivalve mollusks (Taborda et al 2016). Ergasilus xinguensis was described initially on the cichlids Geophagus argyrostictus Kullander, 1991 and Geophagus altifrons Heckel, 1840 from the western Amazon (Taborda et al 2016).…”
Section: Discussionmentioning
confidence: 99%